Impact of Changes to Subsidised Electricity Tariffs on The Welfare Of Households - Andri Yudhi Supriadi; Mohamad Ikhsan; Benedictus Raksaka Mahi; Montty Girianna (ETIKONOMI, 2019)
The subsidized electricity tariff enjoyed by households in Indonesia with an installed capacity of 450 VA and 900 VA has not changed since mid-2003. This subsidy creates an increasing economic burden on the state budget. This study examines the impact of a subsidized electricity tariff increase on subsidized household welfare and the redistribution of subsidy allocation. The analysis divided into two stages: first, estimating household electricity demand for each household group when prices fixed; and second, measuring changes in welfare, inefficiency and the redistribution of subsidy allocations. This empirical study shows that an increase in tariffs causes the welfare of subsidized households to decline. It also demonstrates inefficiency in the allocation of subsidies to the top 20% group with an installed capacity of 450 VA. Besides, subsidized households in the lowest 40% group, which initially only enjoyed 26.26% increased to 34.16% after the tariff increase. On the other hand, the top 20% group, which initially enjoyed the electricity subsidy allocation of 28.74%, decreased to 20.40% after the tariff increase.JEL Classification: D1, D3, D6, I3